TYPOLOGY OF FINANCIAL MANAGEMENT STRATEGIES IN ISLAMIC EDUCATIONAL INSTITUTIONS: A SHARIAH ECONOMIC PERSPECTIVE - Agus Gunawan; M A Tihami; Euis Asyiah; Ombi Romli Ombi; Supianto (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The complexity of the global economy and demands for accountability drive the need for a comprehensive study of financial management strategy typologies that align with the characteristics of Islamic educational institutions and Islamic economic principles. This research aims to identify, classify, and analyze financial management strategy typologies in Islamic educational institutions from an Islamic economic perspective. Effective financial management presents a major challenge for Islamic educational institutions facing global economic complexity and accountability demands, while most still rely on conventional models that have not fully accommodated Islamic values. Using the Systematic Literature Review (SLR) method with the PRISMA protocol, this research analyzed 6 selected articles from 77,522 articles identified from three major academic databases. The results revealed five typologies of financial management strategies in Islamic educational institutions: (1) pure sharia principles-based that emphasize sharia compliance, maqashid sharia, and justice; (2) audit and accountability-based that focus on legal compliance, transparency, and fraud prevention; (3) governance and professionalism-based that prioritize financial manager competence; (4) management function-based that include planning, organizing, implementation, and supervision; and (5) integration of Islamic values into the education system. Despite showing different characteristics, all typologies aim to achieve financial sustainability while maintaining sharia compliance. This research provides a conceptual framework that can serve as a reference in developing adaptive and contextual financial management models according to the characteristics of Islamic educational institutions.